Research in times of crisis : research methods in the time of COVID-19 - Hill, Aaron D.; Lê, Jane K.; McKenny, Aaron F.; O'Kane, Paula; Paroutis, Sotirios; Smith, Anne D. (Bingley, U.K. : Emerald Publishing Limited, 2021)
Research Methodology in Strategy and Management advances understanding of the methods used to study organizations - including managers, strategies, and how firms succeed. Just like the impact felt across many other aspects of life and work, COVID-19 significantly changed the way we approach and conduct research. Many researchers will need to tread unfamiliar methodological ground to address these challenges and seize these opportunities to hone their craft, conducting interesting research in a novel environment. That is precisely why we are making 'crisis' the central focus of this volume. Research in Times of Crisis is an informative book for all academics and researchers working in the fields of management, strategy, international business, entrepreneurship and organization theory.
Chapter 1. Introduction to research methods in times of crisis: The case of Covid-19 / Aaron D. Hill, Jane K. Lê, Aaron F. McKenny, Paula O'Kane, Sotirios Paroutis, and Anne D. Smith -- Chapter 2. Tracking disasters: Researching at the edge of chaos / Robert Gephart -- Chapter 3. The accidental methodologist: Reflections on a serendipitous career / Ann Langley -- Chapter 4. Doing discourse analysis in covid-19 conditions: A foucauldian approach / Suze Wilson -- Chapter 5. Advancing research methods in crisis management / Farhan Iqbal, Jonathan Bundy, and Michael D. Pfarrer -- Chapter 6. Critical perspectives on disaster and crisis research: Revealing and responding to vulnerability / Russell Wordsworth, Colin Michael Hall, Girish Prayag, and Sanna Malinen -- Chapter 7. The bivariate probit model in strategy and management research: Applications and potential / Ke Gong and Scott Johnson -- Chapter 8. Quantifying the robustness of empirical inferences in strategic management: The impact threshold of a confounding variable and robustness of inference to replacement / John R. Busenbark, Kenneth A. Frank, Spiro J. Maroulis, Ran Xu, and Qinyun Lin -- Chapter 9. Research in crisis: Covid-19 and methodological adaptation / Jaewoo Jung, Margaret Koli, Christos Mavros, Johnnel Smith, and Katy Stepanian.
Print version record.
Keywords: elektronické knihy; electronic books; Management -- Research -- Methodology; Strategic planning -- Research -- Methodology; COVID-19 (Disease); Business & Economics -- Research & Development; Research methods: general